Therapeutic Agents Based on DNA Sequence Specific Binding - Pett, Luke; A. Hartley, John; Kiakos, Konstantinos (Current Topics in Medicinal Chemistry, 2015)
DNA interactive agents have been used in the clinical setting for the treatment of cancer since the beginning of modern-era chemotherapy. Despite a shift of focus towards molecular targeted therapy, DNA remains a critical macromolecular target for anti-cancer intervention and the next generation of agents must conform to the optimum combination of increased therapeutic activity and reduced off-target toxicity. We evaluate the potential of non-covalent DNA binding small molecules as “gene-control” agents, exploiting inherent or engineered sequence selectivity, to target critical genomic sequences. In addition we review examples of natural products and synthetic derivatives that exert their activity through sequence specific DNA-covalent modification.
Keywords: Non-covalent binding